El moho blanco - Schwartz, Howard F.; Steadman, James R. (International Center for Tropical Agriculture, 1980)
White mold, caused by the fungus Sclerotinia (Whetzelinia) sclerotiorum, is distributed worldwide and has more than 300 hosts. It infects flowers, cotyledons, seeds, leaves or injured plant tissue. The disease can be controlled by crop rotation, flooding, reduced seeding rates, application of chemical products in the middle of the flowering period, modifying plant architecture and the use of resistant var. Many soil microorganisms are associated with sclerotia and may cause them to degrade or fan to germinate. The symptoms and damage caused by the disease are illustrated in color. (CIAT)